IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA DALAM PENGEMBANGAN KOMPETENSI DOSEN DI LINGKUNGAN AKADEMIK KEBIDANAN DARUSSALAM MARTAPURA - Rusdinor; Khuzaini; Syahrial Shaddiq (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
The quality of higher education, particularly in the health sector, is highly dependent on lecturer competence. This study analyzes the implementation of Human Resource Management (HRM) in developing lecturer competence at the Darussalam Martapura Midwifery Academy, identifying the strategies and obstacles encountered. Employing a descriptive qualitative approach, primary data were obtained through in-depth interviews with key informants and supported by the analysis of real lecturer demographic documents. The HRM implementation at Akbid Darussalam Martapura was found to be effective in maintaining basic pedagogical competence (100% internal workshop participation) but failed in strategic career development. This gap is evidenced by 0% of lecturers holding a Doctoral (S3) degree and a very low realization of external clinical training (5.6%). This failure is attributed to a generally planned Training Needs Analysis (TNA) that is not integrated with specific S3 needs, and a performance evaluation system focusing on administration rather than the real impact of competence improvement. The main root cause is budget and resource limitations hindering the provision of scholarships and financial support for further studies. The current contribution of HRM merely maintains the status quo, demanding a revision of the HRM SOP, allocation of a special budget for S3 scholarships, and improvement of impact-based performance evaluation systems.